PENGGUNAAN AGENS BIOKONTROL Bacillus polymyxa DAN Trichoderma harzianum UNTUK PENINGKATAN MUTU BENIH CABAI DAN PENGENDALIAN PENYAKIT ANTRAKNOSA* - Siregar, Amelia Nani; Ilyas, Satriyas; Fardiaz, Dedi; Murniati, Endang; Wiyono, Suryo (Politeknik Pembangunan Pertanian Bogor, 2007)
Biological seed treatment using B. polymyxa BG25 and T. harzianum Th05 is one ofefforts to improve seed quality and health in order to carry the seed to many places withoutspreading seedborne diseases. This study aimed to improve physical and physiological seedquality and seed health of hot pepper (Capsicum annuum L.) seed as well as eliminateseedborne pathogen caused by antracnose disease (C. capsici). The result indicates that seedtreatment with film coating carrying B. polymyxa and T. harzianum can improve physical seedquality (seeds are more attractive color and shining), physiological quality (increase ofgermination capacity, vigor index, maximum growth potential, uniform growth and dry weightof normal germination) and can reduce of percentage of C. capsici in surface or inside hotpepper seed. This method can be used to protect hot pepper seed and prevent from spreadingseedborne disease.